Математичне моделювання та оптимізація доступу до інформації інтернет-серверів з боку користувачів - Білик, О. З.; Цегелик, Г. Г. (Видавництво Львівської політехніки, 2015)
In this paper the approach to modeling of the optimal user access to the information of remote servers is proposed. The explicit expression of the mathematical expectation of general time, which is necessary for searching of page, is found. It is done as in the case of uniform distribution probability of address to the page such in the case of different laws of non-uniform distribution. The meaning of control parameters, where the mathematical expectation reach the minimum, is found.
Keywords: каталог; блок; сподівання; сторінка; час; розподіл